Trade Unions in Greece - Katsanevas, Theodoros (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1985)
This paper examines the main economie determinants and related factors which have influenced decisevely trade union growth in Greece and the development of the highly complex organizational structure of Greek trade unionism.